2018
DOI: 10.1371/journal.pone.0190391
|View full text |Cite
|
Sign up to set email alerts
|

Study of the influence of socio-economic factors in the international expansion of Spanish franchisors to Latin American countries

Abstract: The saturation of the domestic market is one of the factors which drive firms to expand their business to other markets. Franchising is one of the formats adopted by companies when establishing their internationalization strategy. Spain is a country where franchising is strongly consolidated. This degree of maturity means that many chains seek other countries in which to operate. This work’s specific aims are, on the one hand, to offer a general view of the current situation of Spanish franchisors in Latin Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
2
0
1
Order By: Relevance
“…En este sentido, Khiew et al (2020) destacan la importancia de utilizar técnicas cuantitativas y cualitativas para obtener una visión completa de la organiza-ción. Por otro lado, según Ramírez-Hurtado et al (2018) y Autio y Laamanen (1995) es fundamental involucrar a los empleados en el proceso de evaluación, ya que ellos son quienes mejor conocen los procesos y el funcionamiento interno de la organización.…”
Section: Evaluación De Las Actividades De Transferencia De Tecnologíaunclassified
“…En este sentido, Khiew et al (2020) destacan la importancia de utilizar técnicas cuantitativas y cualitativas para obtener una visión completa de la organiza-ción. Por otro lado, según Ramírez-Hurtado et al (2018) y Autio y Laamanen (1995) es fundamental involucrar a los empleados en el proceso de evaluación, ya que ellos son quienes mejor conocen los procesos y el funcionamiento interno de la organización.…”
Section: Evaluación De Las Actividades De Transferencia De Tecnologíaunclassified
“…Different theoretical approaches have been addressed for the study of the internationalization of franchising for example: An approach based on the organizational factors that allow for the internationalization of the franchise (Alon, Ni, & Wang, 2011;Gillis, Combs, & Ketchen, 2014;Mariz-Pérez & García-Álvarez, 2009;Ni, Alon, & Dant, 2009); external factors at the country level that explain the selection of markets for expansion (Baena, 2012;Baena, 2015;Baena, 2018a;Fladmoe-Lindquist & Jacque, 1995;Madanoglu, Alon, & Shoham, 2017;Melo et al, 2015a;Ramírez-Hurtado, Berbel-Pineda, & Palacios-Florencio, 2018); modes of entry used in its internationalization process (Baena & Cerviño, 2009;Baena & Cerviño, 2014;Baena, 2018a); selection of franchisees abroad (Doherty, 2009;Kedia, Ackerman, & Justis, 1995); influence of the plural form on internationalization (Perrigot, 2008); intention of the franchisors to go abroad (Kedia, Ackerman, & Justis, 1995;Pedro, 2009); franchisors with orientation to the domestic vs. international market (Baena, 2018a;Elango, 2007;Ragazzi Isaac, et al, 2018;Melo et al, 2015b;McIntyre & Young, 2009), typology of international franchises (Navarro García, Rondán Cataluña, & Rodríguez Rad, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They mention that the external factors that drive this expansion to certain countries are: growth of the middle class, growth of the business sector, and the demand for brands in these countries (Hoffman, Watson, & Preble, 2016). Ramírez-Hurtado et al (2018) evaluated the different destination countries Spanish franchisors that want to internationalize toward Latin American markets. They reported that per capita income and market potential imply greater presence of Spanish franchises in those markets.…”
Section: Introductionmentioning
confidence: 99%